EVALUATION OF TRANSFECTED FIBROBLAST CELLS -OF SAHIWAL CATTLE FOR TRANSFECTION / NUCLEAR TRANSFER STUDIES - LAXMI, N ANAND; GUNJAN, G (The Indian Journal of Animal Reproduction, 2023)
The development of an efficient transfection system in livestock cells is an important step towards investigating gene transfer and has impact mainly in agriculture and fundamental biology. The developmental capacity of transfected fibroblast cells isolated from skin piece of ear pinna of adult Sahiwal cattle was studied. Effect of transfection and in vitro culture of cells for six successive passages post transfection was evaluated. Important factors involved in cationic liposome mediated gene transfer were evaluated through in vitro transfection of bovine fibroblast cells. Transfection of plasmid DNA complex (pEGFP and DNAfectin reagent) was evaluated and standardized utilizing the parameters concentration of DNA, lipofection reagent, cell density, and the effect of transfection time on the efficiency of indigenous Sahiwal cattle fibroblasts to express a reporter gene. Stable transfections were conducted using a green fluorescence protein (GFP) reporter plasmid containing the neomycin resistance gene.